The Routledge Handbook of Collective Intelligence for Democracy and Governance - Boucher, Stephen; Hallin, Carina Antonia; Paulson, Lex (Routledge International Handbooks, 2023)
The Routledge Handbook of Collective Intelligence for Democracy and Governance explores the concepts, methodologies, and implications of collective intelligence for democratic governance, in the ﬁrst comprehensive survey of this field. Illustrated by a collection of inspiring case studies and edited by three pioneers in collective intelligence, this handbook serves as a unique primer on the science of collective intelligence applied to public challenges and will inspire public actors, academics, students, and activists across the world to apply collective intelligence in policymaking and administration to explore its potential, both to foster policy innovations and reinvent democracy. The Routledge Handbook of Collective Intelligence for Democracy and Governance is essential reading and an authoritative reference for scholars, students, researchers and practitioners of public policy, public administration, governance, public management, information technology and systems, innovation and democracy as well as more broadly for political science, psychology, management studies, public organizations and individual policy practitioners, public authorities, civil society activists and service providers.